Reliability and Feasibility Considerations in the Assessment of a Malodor Adaptation Technique: A Pilot Study. Issue 1 (2nd July 2018) - Pike, William Y; Proctor, Michael D; Burgess, Deborah N
Abstract: Research often links barriers to optimal human performance of a complex medical task to malodor exposure. Olfactory adaptation, or desensitization to an odorant, may ameliorate performance degradation. Olfactory adaptation is traditionally measured by detection threshold and perceived intensity. Nontraditional measures including stress, confusion, and escape behavior may better reflect impacts on performance but face validity concerns. This article describes a pilot study undertaken to determine what measurements and techniques are best suited and logistically feasible to explore olfactory adaptation with respect to performance of a relevant task. Results of the pilot study confirmed validity of selecting an experimental adaption period a length of time between two previously published results. The study also validated traditional detection threshold and perceived intensity measures and data collection techniques. Electrodermal activity data, a nontraditional measure of stress, proved more promising than inconsistent heart rate or blood pressure. Nontraditional measures of confusion/bewilderment also produced inconsistent outcomes. Perceived workload data were collected for timing purposes; a more homogeneous population may produce more significant results. While preliminary results indicate adaptation may contribute to better complex task performance, follow-on research may proceed using traditional and newly validated measures with the number of subjects necessary to provide statistical confidence.